(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mentoring means sharing knowledge with people around us, it is a professional way of expressing our skills and letting others and ourselves. Educating others with the knowledge we have and that to done in a virtual platform is one of the main reasons of the online mentoring system. These are basically for students nowadays who are into an online platform and looking after the performance has become much more difficult than usual, in this case this system comes handy. This promotes active engagement of students in both academic and their non-academic activities. This Application replaces the conventional and inconvenient method of clearing doubts in classes which involves the mentor and student to be physically present at the same time. In this context arises the importance of our application. This application bridges the existing gap between mentor and students due to the time constraints.